We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
78
1
avatar+1206 

The equation of the hyperbola shown below can be written as \(\frac{(x - h)^2}{a^2} - \frac{(y - k)^2}{b^2} = 1.\)

Find h + k + a + b.

 

 

I've found k to be -1, y to be 3, and a is -2, but what is b and are my answers so far right?

 May 7, 2019
edited by Lightning  May 7, 2019
 #1
avatar+101872 
+1

The center is   (h, k)  = ( -1,3)

 

One of the asymptotic lines- the one with a positive slope - passes through  ( 1, 6)  [ and the center]

 

So.....we can write an equation of this line.....the slope  =  [ 6 - 3 ] / [ 1 - - 1 ]  =  3/2

 

So.....we can write the eqation of this line as

 

y  =  (3/2)(x - -1) + k   =  (3/2) ( x + 1) + 3   =    (b/a) ( x - h) + k

 

So.....

 

a = 2    b   = 3    h  =  -1    and k  =  3        and their sum  = 7

 

Here's a graph : https://www.desmos.com/calculator/lxpgxphby3

 

 

cool cool cool

 May 7, 2019

18 Online Users

avatar
avatar